SOSIALISASI SISTEM INTERGRASI SAPI DAN KELAPA SAWIT DI DESA LUBUK BENTO KECAMATAN PONDOK SUGUH KABUPATEN MUKOMUKO, BENGKULU - Ferry Lismanto Syaiful; Rido Marwiansah (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
Cow and oil palm integration system stands for cattle and oil palm integration system. in general, cow and oil palm integration system is a farming activity that combines cattle and oil palm. System integration the cow and oil palm integration system is positively correlated and mutually beneficial. Seeing the potential of Lubuk Bento village, Bengkulu has a large area of oil palm plantations; this certainly has the potential to be applied to the model cow and oil palm integration system. The objectives of this activity are: 1. to increase the knowledge and understanding of Lubuk Bento village farmers in the application of environmentally friendly agriculture/Good Agricultural Practices (GAP). 2. Empowering farmers/breeders in processing livestock waste into bio urine and organic fertilizer/compost. This activity was carried out in the village of Lubuk Bento, Pondok Suguh District, Mukomuko Regency, Bengkulu. The methods applied in this activity are socialization/ counseling activities and poster distribution cow and oil palm integration system. The activity begins with outreach to community leaders, farmers/breeders, and the local government. Furthermore, outreach activities were carried out for farmers/breeders and the community in Lubuk Bento village. The counseling materials provided are 1. introduction and counseling on bio urine processing, 2. processing livestock waste into organic fertilizer/compost. The results of the activities were that the participants were enthusiastic, received good responses, and even strongly supported this program. Furthermore, this activity can also increase the knowledge and understanding of farmers in processing liquid waste to produce bio urine, and solid waste is processed to produce organic fertilizer/compost. Seeing the high enthusiasm and understanding of farmers/breeders as well as support for this program, it is necessary to continue the application of this cow and oil palm integration system model. Besides that, it is necessary to assist farmers/breeders from the local Department of Agriculture and Livestock in applying the model integration system of cow and oil palm to increase the income of integrated farming system for cattle and oil palm.